Enhanced detection of tuberculous mycobacteria in animal tissues using a semi-nested probe-based real-time PCR - Costa, Pedro (2021)
Bovine tuberculosis has been tackled for decades by costly eradication programs in most developed countries, involving the laboratory testing of tissue samples from allegedly infected animals for detection of Mycobacterium tuberculosis complex (MTC) members, namely Mycobacterium bovis. Definitive diagnosis is usually achieved by bacteriological culture, which may take up to 6-12 weeks, during which the suspect animal carcass and herd are under sanitary arrest. In this work, a user-friendly DNA extraction protocol adapted for tissues was coupled with an IS6110-targeted semi-nested duplex real-time PCR assay to enhance the direct detection of MTC bacteria in animal specimens, reducing the time to achieve a diagnosis and, thus, potentially limiting the herd restriction period. The duplex use of a novel β-actin gene targeted probe, with complementary targets in most mammals, allowed the assessment of amplification inhibitors in the tissue samples. The assay was evaluated with a group of 128 fresh tissue specimens collected from bovines, wild boars, deer and foxes. Mycobacterium bovis was cultured from 57 of these samples. Overall, the full test performance corresponds to a diagnostic sensitivity and specificity of 98.2% (CIP95% 89.4-99.9%) and 88.7% (CIP95% 78.5-94.7%), respectively. An observed kappa coefficient was estimated in 0.859 (CI P95% 0.771-0.948) for the overall agreement between the semi-nested PCR assay and the bacteriological culture. Considering only bovine samples (n = 69), the diagnostic sensitivity and specificity were estimated in 100% (CI P95% 84.0-100%) and 97.7% (CIP95% 86.2-99.9%), respectively. Eight negative culture samples exhibiting TB-like lesions were detected by the semi-nested real-time PCR, thus emphasizing the increased potential of this molecular approach to detect MTC-infected animal tissues. This novel IS6110-targeted assay allows the fast detection of tuberculous mycobacteria in animal specimens with very high sensitivity and specificity, being amenable and cost effective for use in the routine veterinary diagnostic laboratory with further automation possibilities.